Is it true that the Prophet had ever had a Will before the Dying?: Historical Analysis and Analysis of Hadith Science on the Hadiths about Will - Muhamad Ridwan Nurrohman (International Journal of Nusantara Islam, 2017)
The purpose of this paper was to perform verification regarding the will of the Prophet. This study used the approach of hadith science as well as historical analysis to read the available data related to the will of the Prophet. After the research was performed, it was found a conclusion that the Prophet never delegated leadership in a ṣāriḥ way (decisively) to anyone. As for the thing, he firmly bequeathed at the end of his life were (1) to expel Jews, Christians, and polytheists from the Arabian Peninsula and 2) to treat delegates as best as they can. As for the third point, there were those who conclude: a) bequeathing the Quran; b) to send Osama troops; c) to keep the prayers and slaves they had; d) not to make his grave as a place of prayer.